Time-Frequency Characterization of Cerebral Hemodynamics of Migraine Sufferers as Assessed by NIRS Signals. (13th July 2010) - Molinari Molinari, Filippo Filippo; Rosati Rosati, Samanta Samanta; Liboni Liboni, William William; Negri Negri, Emanuela Emanuela; Mana Mana, Ornella Ornella; Allais Allais, Gianni Gianni; Benedetto Benedetto, Chiara Chiara
Abstract : Near-infrared spectroscopy (NIRS) is a noninvasive system for the real-time monitoring of the concentration of oxygenated (O 2 Hb ) and reduced (HHb) hemoglobin in the brain cortex. O 2 Hb and HHb concentrations vary in response to cerebral autoregulation. Sixty-eight women (14 migraineurs without aura, 49 migraineurs with aura, and 5 controls) performed breath-holding and hyperventilation during NIRS recordings. Signals were processed using the Choi-Williams time-frequency transform in order to measure the power variation of the very-low frequencies (VLF: 20–40 mHz) and of the low frequencies (LF: 40–140 mHz). Results showed that migraineurs without aura present different LF and VLF power levels than controls and migraineurs with aura. The accurate power measurement of the time-frequency analysis allowed for the discrimination of the subjects' hemodynamic patterns. The time-frequency analysis of NIRS signals can be used in clinical practice to assess cerebral hemodynamics.